Miniaturization of spectrophotometry based on micro flow analysis using norfloxacin as less-toxic reagent for iron determination - Kanyarak Prasertboonyai (2018)
© 2015 Elsevier B.V. All rights reserved. A micro flow analysis (μFA) system has been designed and fabricated for determination of total iron. The system consists of a microchannels fabricated by etching the polymethyl methacrylate (PMMA) by using laser ablation techniques and a sealed polydimethylsiloxane (PDMS) as top plate. The PMMA micro-flow was topped with a home-made polydimethylsiloxane (PDMS) micro-flow through cell, which was integrated with light emitting diode (LED) as light source and a USB 2000 spectrometer as detector. The proposed μFA system was applied to determination of Fe(III) using norfloxacin as a less-toxic complexing agent in an acetate buffer solution pH 4.0, resulting in a yellow colored complex which gave the maximum absorption at 430 nm. Under the optimum conditions, a linear calibration graph was obtained in the concentration range of 0.20-5.00 mg L-1. The limit of detection (LOD, defined as 3σ) and limit of quantification (LOQ, defined as 10σ) were 0.12 and 0.45 mg L-1, respectively. The relative standard deviation (R.S.D.) for repeatability and reproducibility were less than 1.50% and 1.24% (n = 11) for 0.2 mg L-1 and 1.0 mg L-1 Fe(III), respectively. The proposed method was successfully applied to the determination of total iron in water samples, validated by the FAAS standard method after digestion by HNO3 and H2O2.